The Influence of Religiosity, Trust, Knowledge and Location on People Interest in Saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis - Azizatul Aulia; M. Alkadri Perdana (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
This study aims to determine the influence of religiosity, trust, knowledge and location on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The number of samples in this study was 100 respondents by distributing questionnaires to people who saved at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The research method used is a quantitative approach using a non-probability sampling method with purposive sampling and the analysis method is multiple linear regression. The results of this study indicate that partially religiosity, trust, knowledge and location variables have a significant influence on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. Simultaneously, the variables of religiosity, trust, knowledge, and location have a significant influence on people interest in saving at Bank Syariah Indonesia Sub-Branch Office Bengkalis. The coefficient of determination of religiosity, trust, knowledge and location is 66.1% of the interest in saving.Keywords: Religiosity, Trust, Knowledge and Location